2021
DOI: 10.1021/acsinfecdis.1c00394
|View full text |Cite
|
Sign up to set email alerts
|

Oral Efficacy of a Diselenide Compound Loaded in Nanostructured Lipid Carriers in a Murine Model of Visceral Leishmaniasis

Abstract: Leishmaniasis urgently needs new oral treatments, as it is one of the most important neglected tropical diseases that affects people with poor resources. The drug discovery pipeline for oral administration currently discards entities with poor aqueous solubility and permeability (class IV compounds in the Biopharmaceutical Classification System, BCS) such as the diselenide 2m , a trypanothione reductase (TR) inhibitor. This work was assisted by glyceryl palmitostearate and diethylene gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Although there are no data regarding the accumulation of these nanocarriers in the primary organs targeted by visceral leishmaniasis (e.g. liver, spleen, and bone marrow), only selenocompunds that reached plasma selenium concentrations higher than the in vitro intramacrophage IC 50 index showed significant antileishmania activity in infected animals (Etxebeste-Mitxeltorena et al, 2021). Singh et al also developed a biocompatible and stable AmpB lipid-based nanocarrier for oral administration by grafting carboxymethyl chitosan (CMC) on the surface of lipid nanoparticles (CMC-AmpB-LV) (Singh et al, 2022).…”
Section: Leishmaniasismentioning
confidence: 99%
“…Although there are no data regarding the accumulation of these nanocarriers in the primary organs targeted by visceral leishmaniasis (e.g. liver, spleen, and bone marrow), only selenocompunds that reached plasma selenium concentrations higher than the in vitro intramacrophage IC 50 index showed significant antileishmania activity in infected animals (Etxebeste-Mitxeltorena et al, 2021). Singh et al also developed a biocompatible and stable AmpB lipid-based nanocarrier for oral administration by grafting carboxymethyl chitosan (CMC) on the surface of lipid nanoparticles (CMC-AmpB-LV) (Singh et al, 2022).…”
Section: Leishmaniasismentioning
confidence: 99%
“…This might be related to an insufficient amount of surfactant to cover the nanoparticles at low concentrations; therefore, their stability decreases, which results in coalescence and aggregation of the nanoparticles [43]. Also, it has been reported that Z av tends to be influenced by lipid and surfactant concentrations due to its straight relation with viscosity factor, which increases if lipid concentrations are near or above 10 %, resulting in an average size increase [44]. According to PI results, the surfactant concentration highly influences PI, which may be explained by recent reports showing that Lutrol ® F68 creates a stabilizer layer in the nanoparticle surface, leading to PI values around 0.2 [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, NLCs were prepared for oral administration with diselenide, a Biopharmaceutics Classification System (BCS) class IV drug . To improve the bioavailability and efficacy of the drug, NLCs were prepared using glyceryl palmitostearate and diethylene glycol monoethyl ether.…”
Section: Nanodrug Delivery Systems Utilized During Leishmaniasis Trea...mentioning
confidence: 99%
“…Recently, Jesus and co-workers 64 have reported ursolic acid (UA)-loaded NLCs to treat V.L. The developed NLCs had a particle size of 266 nm with a spherical morphology and smooth surface.…”
Section: Nanodrug Delivery Systems Utilized During Leishmaniasis Trea...mentioning
confidence: 99%